America's other Muslims Imam W.D. Mohammed, Islamic reform, and the making of American Islam - Fraser-Rahim, Muhammad (Black diasporic worlds., 2020)
Fraser-Rahim spotlights the emergence of an American school of Islamic thought, which was created and established by the son of the former Nation of Islam leader. W.D. Mohammed rejected his father's teachings and embraced normative Islam on his own terms while balancing classical Islam and his lived experience of Islam in the diaspora.